Chiral phosphonate internucleotide linkage: a promising modification for chimeric oligonucleotides? - Liboska, Radek; Petrová, Magdalena; Pohl, Radek; Budesínsky, Milos; Hurychová, Vladimíra; Rosenberg, Ivan (Nucleic acids symposium series, 2008)
We have synthesized two different groups of oligonucleotides containing chiral isopolar nonisosteric phosphonate internucleotide linkages, and studied their properties in combination with natural phosphodiester ones. The improved synthetic procedures for the monomers preparation are also reported.
Keywords: endoribonukleasy; Oligodeoxyribonucleotides; Phosphorous Acids; isomerie; DNA; Endoribonucleases; Isomerism; kyseliny fosforité; RNA; oligodeoxyribonukleotidy